Siklosporin mengubah farmakokenetik sulfametizol pada tikus - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
ABSTRACT This work aims to study the pharmacokinetics of sulfamethizole in rats pre-treated with cyclosporin, and to seek correlations between total clearance (CL/F) and T1/2 elimination of the drug with creatinine clearance (CLcr,). Female Wistar rats were each injected with the sulfamethizole (40 mg/kg